2019
DOI: 10.1186/s13104-019-4095-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sexual maturation status on the relationship between body adiposity indicators and age: a cross-sectional study

Abstract: ObjectivesTo determine the influence of sexual maturation status on adiposity indicators of children and adolescents.Results2412 individuals participated, 1285 (47.4%) males and 1408 (52.6%) females. There was moderate to weak correlation between age and adiposity indicators for both sexes. By analyzing the relationship between age and body fat indexes adjusted for Sexual Maturation Status, several changes were observed, mainly in girls. Precocious maturation was associated with increased adiposity indicators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…Chiocca et al [55] showed that during treatment FFM decreased and %FM increased, whereas BMI did not change at adult height and suggested that the findings may be related to shortening of the prepubertal developmental window for body composition. In an earlier study, Chiumello et al [45] showed a small group of children with CPP was slightly fatter with less lean compartment mass than age- matched controls at adult height. They suggested that reduction in the time for prepubertal lean mass development might lead to reduced lean mass in this group of patients [56].…”
Section: Body Composition In Precocious Puberty and The Effect Of Gnr...mentioning
confidence: 94%
See 1 more Smart Citation
“…Chiocca et al [55] showed that during treatment FFM decreased and %FM increased, whereas BMI did not change at adult height and suggested that the findings may be related to shortening of the prepubertal developmental window for body composition. In an earlier study, Chiumello et al [45] showed a small group of children with CPP was slightly fatter with less lean compartment mass than age- matched controls at adult height. They suggested that reduction in the time for prepubertal lean mass development might lead to reduced lean mass in this group of patients [56].…”
Section: Body Composition In Precocious Puberty and The Effect Of Gnr...mentioning
confidence: 94%
“…Recently, Takahashi et al [45] showed that precocious sexual maturation was associated with increased adiposity indicators only in girls, whereas late maturation was associated with decreased adiposity in both sexes. During treatment with GnRHa therapy, some studies showed no change [1], while some showed an increase in BMI especially in the first year of treatment [46].…”
Section: Effects Of Gnrha Treatment On Bmi Fat Mass and Fat-free Massmentioning
confidence: 99%
“…The other variables that entered the model were weight, Xc, sex, and age. Considering that adolescence is a phase of profound morphological changes, which include body composition ( 4 , 50 , 51 ), and that the age at which each stage of puberty occurs can vary considerably ( 52 ), we listed the pubertal stage among the possible independent variables; however, this variable was not included in the model by the stepwise regression. The same was verified in the other studies that proposed predictive equations of FFM by BIA in adolescents, which we tested for validity in the sample of this study ( 15 , 23 , 24 , 40 – 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gonçalves et al [16] state there is an increase in body mass as the pre-pubertal individual moves to the pubescent and post-pubescent stages. As for body composition, it is believed that the higher percentage of body fat in pre-infants, concerning children, is related to the process of energy repletion, characteristic of the pre-pubertal phase, and so necessary for future development (pubertal spurt) [17]. The lower percentage of fat mass found in children's gymnasts can also be linked to the stage of sexual maturation, since practically half of the group is pubescent, and according to Fidencio et al [18], this is the stage in which the spurt usually occurs, favoring the reduction of fat mass.…”
Section: Discussionmentioning
confidence: 99%